When songs replace Scripture: contemporary worship music and the transformation of congregational formation - Tang, Michael Chee Man (Theology, 2026)
This article examines how contemporary worship music’s (CWM’s) emphasis on personal emotion over biblical content affects congregational spiritual formation. While offering genuine benefits for emotional engagement, CWM’s predominant focus on subjective experience may undermine biblical literacy and theological understanding. Drawing on historical comparison with earlier forms of liturgical standardization, sociological analysis of habitus formation and examination of musical–theological structures, this article argues that the current concentration of worship music production creates both unprecedented challenges and opportunities for Christian discipleship. Using evidence from recent empirical research, this article demonstrates how market-driven liturgical uniformity differs from historical ecclesiastical standardization and shapes congregational theological imagination in distinct ways. Churches must balance emotional authenticity with scriptural depth to ensure that worship serves comprehensive formation. This balance prevents worship from merely facilitating religious expression rather than nurturing discipleship.